Effects of digital health for self-management in adult with type 2 diabetes: A systematic literature review - Shuai, Ziying; Murray , Dr. Martin (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2024)
Background: Digital health services offer effective solutions to support self-management among adults with T2DM. These tools enable individuals to continuously collect longitudinal data on their daily behaviours and clinical datas, facilitating ongoing health assessments and timely responses to T2DM management. Methods: A systematic review of English peer-reviewed articles was conducted, involving a comprehensive literature search of PubMed, MEDILINE, CINAHL, Web of Science spanning from 2013 to 2023. Inclusion criteria comprised studies focusing on digital health interventions for self-management of T2DM in adults aged 18 years and above. Results: Sixteen articles were identified based on the inclusion and exclusion criteria, as well as the quality evaluation standards. The review underscores the transformative potential of digital health technologies, enabling not only the monitoring and management of blood glucose levels, dietary intake, body weight control, medication adherence, and physical activities, but also facilitating personalised health information dissemination, professional education and coaching, and effective two-way communication between adults with T2DM and healthcare professionals, these features empower individuals and enhance their autonomy and engagement in managing their T2DM health. Conclusion: This review has systematically evaluated the effectiveness and application features of digital health interventions for self-management among adults with T2DM. It identifies self-management behaviours tested in the reviewed literature and assesses the limitations of these studies. Furthermore, this review comprehensively explored the barriers, challenges, facilitators, research gaps, and future policy and practice directions associated with advanced technology-enabled self-care solutions for this population. Keywords: Digital Health Services; Effects And Barriers; Self-Management; Systematic Literature Review; Type 2 Diabetes.